Bridging the Gap: OCR and LLM-Assisted Tools for Integrating Commercial Game-Based Language Learning into Formal Instruction - Tornberg, Jesse (My University, 2026)
Commercial off-the-shelf (COTS) games have attracted growing interest as language learning environments due to their motivational affordances, authentic linguistic input, and capacity for meaningful communicative interaction. However, a structural gap persists between autonomous gameplay and formal language instruction: existing assistive tools serve independent learners but lack any mechanism for instructor oversight or curricular alignment. This thesis addresses that gap through two complementary strands of inquiry. A systematic literature review of 24 empirical studies examines which games have been used in Digital Game-Based Language Learning (DGBLL) research, on what grounds they were selected, and what limitations they consistently present. A qualitative empirical component consisting of semi-structured interviews with four university-level Japanese language educators then investigates whether a purpose-built bridge tool — integrating Optical Character Recognition (OCR) and Large Language Model (LLM) technology — would be considered a pedagogically viable solution. The literature review finds that game selection is driven primarily by motivational and social factors rather than pedagogical design, and that the resulting scaffolding gap and instructional opacity are consistent barriers across studies. Interview findings confirm that educators are open to game-based learning but require morphological scaffolding over full-sentence translation, curriculum-filtered session reporting, and teacher-directed grammar watchlists before autonomous gameplay can be considered a legitimate academic activity. Together, these findings suggest that the barrier to integrating COTS games into formal instruction is not primarily technical but organizational: the infrastructure for transparency and curricular alignment is the missing link between autonomous play and institutional recognition.

Kaupalliset pelit ovat herättäneet kasvavaa kiinnostusta kielten oppimisympäristöinä niiden tarjoamien motivaatiotekijöiden, autenttisen kielenkäytön, ja vuorovaikutuksen mahdollistamisen vuoksi. Itsenäisen pelaamisen ja kielenopetuksen välillä on kuitenkin puuttuva osa: olemassa olevat avustavat työkalut palvelevat itsenäisiä oppijoita, mutta niistä puuttuu pedagoginen seuranta, opettajan näkyvyys, ja opetussuunnitelman seuranta. Tämä tutkielma käsittelee tätä puuttuvaa osaa kahden toisiaan täydentävän tutkimuslinjan avulla. Systemaattinen kirjallisuuskatsaus 24 empiirisestä tutkimuksesta tarkastelee, mitä pelejä on käytetty digitaalisen pelipohjaisen kielenoppimisen (DGBLL) tutkimuksessa, millä perusteilla ne valittiin ja mitä rajoituksia niissä on havaittu. Tutkielman empiirinen osa, joka koostuu puolistrukturoiduista haastatteluista neljän yliopistotason japanin kielen opettajan kanssa. Haastattelut vastaavat siihen, että olisiko tarkoitukseen rakennettu työkalu - joka yhdistää optisen tekstintunnistuksen (OCR) ja suuren kielimallin (LLM) teknologian –pedagogisesti toteuttamiskelpoinen ratkaisu. Kirjallisuuskatsauksessa todetaan, että pelien valintaa ohjaavat ensisijaisesti motivoivat ja sosiaaliset tekijät pikemminkin kuin pedagoginen suunnittelu, ja että siitä johtuva tukirakenteiden puute ja opetuksen läpinäkymättömyys ovat toistuvia esteitä eri tutkimuksissa. Haastattelutulokset vahvistavat, että kouluttajat ovat avoimia pelipohjaiselle oppimiselle, mutta tarvitsevat morfologista tukea kokonaisten lauseiden kääntämisen sijaan. Opetussuunnitelman mukaan suodatettu istuntoraportointi ja opettajan ohjaamien kieliopin seurantalistojen luominen ovat myös osa ratkaisua, ennen kuin pelaamista voidaan pitää opiskeluna. Yhdessä nämä havainnot viittaavat siihen, että este kaupallisten pelien integroinnille opetukseen ei ole ensisijaisesti teknisellä, vaan organisoinnin tasolla: pelaamisen läpinäkyvyyden ja opetussuunnitelmaan mukauttamisen mahdollistava infrastruktuuri, tässä tapauksessa erillisenä työkaluna on puuttuva pala itsenäisen pelaamisen ja institutionaalisen tunnustuksen välillä.
Keywords: digital game-based language learning; DGBLL; commercial off-the-shelf games; COTS; language acquisition; OCR; large language models; language learning tools; videopelit; pelipohjainen oppiminen; kieltenopiskelu; optinen tekstintunnistus (OCR); suuret kielimallit (LLM); kielenoppimistyökalut